Child Protection Special Interest Group 2018
DOI: 10.1136/archdischild-2018-rcpch.138
|View full text |Cite
|
Sign up to set email alerts
|

G142 Female genital mutilation surveillance in under 16 years olds in the uk and ireland

Abstract: AimsFemale genital mutilation (FGM) is the name given to procedures that involve partial or total removal or other injury to the female genitalia for nonmedical reasons. This study describes the presentation, incidence and clinical management of children with FGM in the UK and Republic of Ireland (ROI).MethodsCases of FGM were reported using the established national British Paediatric Surveillance Unit (BPSU) reporting system. The data period is from November 2015-November 2017 with a 12 month follow up.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a different report, 15 out of 18 (86%) children with confirmed FGM seen in a clinic for children with suspected FGM had been cut before coming to the UK 10. Furthermore, paediatricians reported 61 confirmed cases among under 16s to the British Paediatric Surveillance Unit over the two years to November 2017, most done before UK entry 11…”
Section: Unsuccessful Prosecutionsmentioning
confidence: 99%
“…In a different report, 15 out of 18 (86%) children with confirmed FGM seen in a clinic for children with suspected FGM had been cut before coming to the UK 10. Furthermore, paediatricians reported 61 confirmed cases among under 16s to the British Paediatric Surveillance Unit over the two years to November 2017, most done before UK entry 11…”
Section: Unsuccessful Prosecutionsmentioning
confidence: 99%
“…The editorial mentioned the interim findings of a study by the British Paediatric Surveillance Unit, which found only 61 “confirmed cases” of FGM among those notified in a two year period 210…”
mentioning
confidence: 99%